Laser Synthesis of Platinum Single-Atom Catalysts for Hydrogen Evolution Reaction - Hengyi Guo; Lingtao Wang; Xuzhao Liu; Paul Mativenga; Zhu Liu; Andrew G. Thomas (Nanomaterials)
Platinum (Pt)-based heterogeneous catalysts show excellent performance for the electrocatalytic hydrogen evolution reaction (HER); however, the high cost and earth paucity of Pt means that efforts are being directed to reducing Pt usage, whilst maximizing catalytic efficiency. In this work, a two-step laser annealing process was employed to synthesize Pt single-atom catalysts (SACs) on a MOF-derived carbon substrate. The laser irradiation of a metal–organic framework (MOF) film (ZIF67@ZIF8 composite) by rapid scanning of a ns pulsed infrared (IR; 1064 nm) laser across the freeze-dried MOF resulted in a metal-loaded graphitized film. This was followed by loading this film with chloroplatinic acid (H2PtCl6), followed by further irradiation with an ultraviolet (UV; 355 nm) laser, resulting in pyrolysis of H2PtCl6 to form the SAC, along with a further reduction of the MOF to form a Pt-decorated laser-induced annealed MOF (Pt-LIA-ZIF8@ZIF67). The Pt-LIA-ZIF8@ZIF67 catalyst with a Pt loading of 0.86 wt. % exhibited exceptionally high activity for the HER in acidic conditions. The atomically dispersed Pt on the carbon substrate exhibited a small overpotential of 68.8 mV at 10 mA cm−2 for the hydrogen evolution reaction with a mass activity 20.52 times that of a commercial Pt/C catalyst at an overpotential of 50 mV vs. RHE. Finally, we note that the synthesis method is simple, fast, and versatile, and potentially scalable for the mass production of SACs for electrocatalytic applications.